Do Males and Females Differ in Terms of Their KAP Regarding Halal Pharmaceuticals? - Saleha Sadeeqa; Azmi Sarriff (International Journal of Public Health Science (IJPHS), 2014)
There is an increasing awareness amongst Muslim consumers to avoid all items containing  non-Halal ingredients including medications. Male and female are different both biologically and psychologically, it therefore, needed for a study to compare KAP of males and females regarding  Halal pharmaceuticals. Methods:This was a cross-sectional study using a structured , self-administered questionnaires to compare the knowledge, attitude & perception regarding Halal pharmaceuticals, among males and females in Penang state of Malaysia. Results revealed that there is no significance difference in the knowledge, attitude and perception of males and females. This is concluded that males and females are equally aware and have same attitude and perception regarding Halal pharmaceuticals. P value of .05 or less was taken as statistically significant.